Pengaruh Motivasi Terhadap Peningkatan Produktivitas Kerja Karyawan PT. Mektek Tanjung Lestari Kabupaten Tabalong - Muhammad Haris Syafitri; Hairul Hairul; Husnurrofiq Husnurrofiq; Farida Yulianti; Edy Mahfuz; Periyadi Periyadi (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2024)
This research on work motivation towards employee performance of PT. Adaro Indonesia Tabalong Regency aims to simultaneously determine and analyze the influence of intrinsic motivation and extrinsic motivation towards increasing employee work productivity of PT. Mektek Tanjung Lestari Tabalong Regency, to determine and partially analyze the influence of intrinsic motivation and extrinsic motivation towards increasing employee work productivity of PT. Mektek Tanjung Lestari Tabalong Regency and to determine and analyze the variables of intrinsic motivation and extrinsic motivation that have a dominant influence on increasing employee work productivity. The research will be conducted with a quantitative approach, namely all information is presented in the form of numbers, starting from data collection, interpretation of the data, the appearance of the results and its analysis based on statistical analysis. The population used in this study was taken from the overall data of employees working at PT. Mektek Tanjung Lestari Tabalong Regency with a total of 76 people. While the samples used were all 64 people using multiple regression data analysis. The results of the analysis show that: (1) the calculated F value is 25.422 with a significance level of 0.000 <5%. Because the significant probability is less than 0.05, Ho is rejected and Ha is accepted. (2) Intrinsic motivation (X1) obtained a test statistic of t = 2.667 with a significance of 0.010. The coefficient of the t test result at a significance level of 0.010 is smaller than 0.05 (>5%). For the calculated t produced is 2.667, while for the t table it is 1.99962. Because the calculated t value is greater than the t table (2.667 > 1.99962), it can be concluded that intrinsic motivation (X1) has a positive and significant influence on employee work productivity (Y). (3) Extrinsic motivation (X2) shows a significance level of 0.001 which is smaller than 0.05 (<5%). Because the calculated t value is greater than the t table (3.358 > 1.99962), it can be concluded that extrinsic motivation (X2) has a positive and significant influence on employee work productivity (Y). (4) The extrinsic motivation variable (X2) is more dominant in terms of work productivity (Y) of employees of PT. Mektek Tanjung Lestari, Tabalong Regency, with a Standardized Coefficients value of 0.414, including a strong correlation value.